Determinants of suboptimal blood pressure control in a multi‐ethnic population: The Healthy Life in an Urban Setting (HELIUS) study. Issue 5 (6th March 2021) - van der Linden, Eva L.; Collard, Didier; Beune, Erik J. A. J.; Nieuwkerk, Pythia T.; Galenkamp, Henrike; Haafkens, Joke A.; Moll van Charante, Eric P.; van den Born, Bert‐Jan H.; Agyemang, Charles
Abstract: Among ethnic minority groups in Europe, blood pressure (BP) control is often suboptimal. We aimed to identify determinants of suboptimal BP control in a multi‐ethnic population. We analyzed cross‐sectional data of the Healthy Life in an Urban Setting (HELIUS) study, including 3571 participants aged 18‐70 with prescribed antihypertensive medication, of various ethnic backgrounds (500 Dutch, 1052 African Surinamese, 656 South‐Asian Surinamese, 637 Ghanaian, 433 Turkish, and 293 Moroccan) living in Amsterdam, the Netherlands. 53.3% of the population had suboptimal BP control, defined as BP ≥140/90 mmHg despite prescribed antihypertensives. Using multivariate logistic regression analysis, female sex (OR 0.50, 95%CI 0.43‐0.59), being married (0.83, 0.72‐0.96), smoking (0.78, 0.65‐0.94), alcohol intake (0.80, 0.66‐0.96), obesity (1.67, 1.35‐2.06), cardiovascular disease (CVD) history (0.56, 0.46‐0.68), non‐adherence to antihypertensives (1.26, 1.00‐1.58), and family history of hypertension (1.19, 1.02‐1.38) were identified to be independently associated with suboptimal BP control in the total population. In the ethnic‐stratified analysis, factors associated with better BP control were female sex (all ethnic groups), smoking (Turks), and CVD history (Dutch, South‐Asian Surinamese, and African Surinamese), whereas factors associated with suboptimal BP control were older age (Turks), obesity (Dutch, African Surinamese, Ghanaian, and Turks), and non‐adherence to antihypertensives (Dutch). In conclusion, our analysis identifies several key determinants that are independently associated with suboptimal BP control in a multi‐ethnic population, with some important variations between ethnic groups. Targeting these determinants may help to improve BP control. Abstract : Among ethnic minority groups in Europe, blood pressure (BP) control is often suboptimal. We assessed determinants of suboptimal BP control in a large multi‐ethnic population with prescribed BP‐lowering medication and found several key determinants that are independently associated with suboptimal BP control, with some important variations between ethnic groups.